Baccolet [sic] Beach Tobago - (:unkn) unknown (Pereira and Co. Ltd.,[Trinidad and Tobago], 2011)
The postcard offers a scenic view of Bacolet Beach in Tobago. This postcard, which is postmarked 1967, is addressed to Mrs A Sluis of Chicago, Illinois, United States of America and affixed is a 12 cents Trinidad and Tobago postage stamp.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; 1967